Paradigm Shift from Traditional to Viral Marketing: Cost Challenges, Cultural Dynamics and New Strategies in Asian Film Marketing (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The global film industry has undergone a profound transformation in its marketing strategies, accelerated by the proliferation of Web 2.0 technologies and the dominance of social media platforms. Traditional marketing channels, television, radio, and print have been progressively supplanted by viral marketing strategies that promise large-scale audience reach at substantially lower costs. This paper examines the paradigm shift from traditional to viral marketing within the Asian film industry, with particular attention to cost challenges, cultural dynamics, and emerging technological strategies. Employing a qualitative approach grounded in systematic document review, this study applies a structured two-stage screening and quality appraisal procedure informed by PRISMA best practices to synthesize existing scholarship from Scopus-indexed academic journals and peer-reviewed scholarly books on social media marketing, viral communication, electronic word-of-mouth (eWOM), cultural dimensions of film consumption, and technology-driven marketing innovation. Findings reveal that while platforms such as TikTok, Instagram, Weibo, and Douyin offer unprecedented cost efficiency and organic reach, viral campaigns are constrained by the ephemerality of audience interest, the so-called ‘15 minutes of fame’ phenomenon. Critically, the study demonstrates that viral marketing dynamics, cost structures, and platform cultures differ substantially across Asian national markets, including China, Malaysia, India, South Korea, Indonesia, and Vietnam, and that no single regional model adequately captures this heterogeneity. The emergence of Artificial Intelligence (AI), Big Data analytics, predictive modelling, and blockchain-based marketing systems further reshapes the strategic landscape. While the exclusive reliance on secondary sources is acknowledged as a limitation, the study incorporates comparative case evidence from multiple Asian film industries to ground theoretical insights in documented real-world outcomes. This study contributes to the growing body of scholarship on digital film marketing in Asian contexts and offers practical implications for producers, distributors, and marketing professionals operating in the post-Web 2.0 media economy.